Clinical Study on Simple Myopia with Reference To the Effect of Triphala Ghreeta - Biswal, Dr. Adikanda; Mohanty, Pradyut Kumar (International Journal of Innovative Research in Medical Science, 2017)
Myopia representing the characteristics of indistinct distant vision. It is a commonly available condition, taken for the research study. In low degree myopia, the only complaint is inability to see the distant object clearly. In higher degree of myopia blurring of objects, and difficulty in maintaining near vision with comfort for long also.in this case by the help of ayurveda we prepared a drug triphala ghreeta and used by process called netra tarpana. This for cure of myopia not for the correction of refractive error.